Insight into the Association between Slitrk Protein and Neurodevelopmental and Neuropsychiatric Conditions - Nidhi Puranik; Minseok Song (Biomolecules)
Slitrk proteins belong the leucine-rich repeat transmembrane family and share structural similarities with the Slits and tropomyosin receptor kinase families, which regulate the development of the nervous system. Slitrks are highly expressed in the developing nervous system of vertebrates, modulating neurite outgrowth and enhancing synaptogenesis; however, the expression and function of Slitrk protein members differ. Slitrk protein variations have been associated with various sensory and neuropsychiatric conditions, including myopia, deafness, obsessive–compulsive disorder, autism spectrum disorders, schizophrenia, attention-deficit/hyperactivity disorder, glioma, and Tourette syndrome; however, the underlying mechanism remains unclear. Therefore, the Slitrk family members’ protein expression, roles in the signaling cascade, functions, and gene mutations need to be comprehensively studied to develop therapeutics against neurodegenerative diseases. This study presents complete and pertinent information demonstrating the relationship between Slitrk family proteins and neuropsychiatric illnesses. This review briefly discusses neurodevelopmental disorders, the leucine-rich repeat family, the Slitrk family, and the association of Slitrk with the neuropathology of representative disorders.